Effect of National Health Insurance Scheme on Healthcare Utilization Patterns and Quality of Services in FCT, Nigeria - Abah, Ali Peter; Ojobo , James; Okolobia, Omadachi (Kashere Journal of Politics and International Relations, 2024)
This study assesses the effect of National Health Insurance Scheme (NHIS) on healthcare utilization patterns and quality of services in the Federal Capital Territory (FCT), Nigeria. The survey data reveals that enrollment in NHIS has positively influenced the willingness to seek prompt medical help and utilize preventive healthcare services. However, the increase in frequency of healthcare facility visits and reduction in out-of-pocket expenses remain areas with mixed perceptions. Also, the result shows that NHIS has led to improved interactions with healthcare providers and increased access to a broader range of services. Yet, there is notable dissatisfaction with the overall quality of care and the availability of advanced diagnostic tests and treatments. While there are improvements in communication with healthcare providers and reduced waiting times, access to specialised healthcare providers and adherence to treatment protocols are areas needing attention. To enhance the effectiveness of NHIS and address the identified challenges, the following recommendations among others are proposed: Government should embark on sensitization exercise to increase awareness about benefits of NHIS, expand the network of healthcare facilities, especially in underserved areas, reduce travel distances and improve accessibility, invest in mobile health units to serve remote regions to ensure that even the most isolated populations have access to necessary healthcare services, ensure continuous training and professional development for healthcare providers to improve competency, professionalism, and patient interactions and invest in modern medical equipment and advanced diagnostic tools to enhance the quality of care provided in NHIS-covered facilities.